Presentation: A Kriging Approach to Model Updating for Damage Detection - Dessena, Gabriele (Cranfield University, 2022)
This are the presentation slides for the presentation delivered on the 4.7.2022 at the 10th European Workshop on Structural Health Monitoring in Palermo, Italy. The presentation refers to the "A Kriging Approach to Model Updating for Damage Detection" paper that can be found at https://doi.org/10.1007/978-3-031-07258-1_26
Keywords: Kriging'; 'Finite Element Model'; 'Finite Element Method'; 'Model Updating'; 'Structural Health Monitoring'; 'Modal Analysis'; 'MTMAC'; 'Damage Detection'